2020
DOI: 10.1017/inp.2020.23
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating winter annual grass control and native species establishment following applications of indaziflam on rangeland

Abstract: Indaziflam, a preemergent (PRE) herbicide option for weed management on rangeland and natural areas, provides long-term control of invasive winter annual grasses (IWAGs). Since indaziflam only provides PRE control of IWAGs, postemergent (POST) herbicides such as glyphosate can be mixed with indaziflam to control germinated IWAG seedlings. Field trials were conducted at three sites on the Colorado Front Range to evaluate glyphosate dose required to provide adequate POST IWAG control, and compare long-term Bromu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
6
16
0
Order By: Relevance
“…Established perennial graminoid richness and Shannon's diversity were largely unaffected by indaziflam (P = 0.96 and P = 0.50, respectively) (Tables 2 and 3, Supplementary Figure S1), as expected from previous studies (Clark et al 2019(Clark et al , 2020. Perennial forb mean species richness was lower in sprayed plots (P < 0.01) and under high invasion (P = 0.02), decreased with elevation (P < 0.01), and differed between years (P = 0.01; Table 3, Supplementary Figure S1).…”
Section: Perennial Species Responsesupporting
confidence: 83%
See 2 more Smart Citations
“…Established perennial graminoid richness and Shannon's diversity were largely unaffected by indaziflam (P = 0.96 and P = 0.50, respectively) (Tables 2 and 3, Supplementary Figure S1), as expected from previous studies (Clark et al 2019(Clark et al , 2020. Perennial forb mean species richness was lower in sprayed plots (P < 0.01) and under high invasion (P = 0.02), decreased with elevation (P < 0.01), and differed between years (P = 0.01; Table 3, Supplementary Figure S1).…”
Section: Perennial Species Responsesupporting
confidence: 83%
“…In areas where the seedbank is composed mostly of nonnative species that have formed persistent soil seedbanks, indaziflam is a valuable tool to deplete the seedbank of target species before active revegetation efforts (Clark et al 2020). However, in areas with minimal infestations, an existing diverse plant community, and therefore likely a diverse seedbank, the use of indaziflam and its impacts on the seedbank of nontarget species should be carefully considered before broadscale use.…”
Section: Impacts Of Indaziflam On Soil Seedbank Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option would be to wait (2–5 years) until the indaziflam activity level has decreased, and then seed native species. One study showed success seeding in the fall following a spring application of indaziflam (Clark et al., 2020). Both approaches could potentially lead to restoration seeding success, and long‐term invasive annual grass control, but waiting to seed several years after herbicide application could potentially result in large areas of bare ground and eventual erosion on sloped or high wind areas.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have compared invasive annual grass control by herbicide (Applestein, Germino, & Fisk, 2018; Clements, Harmon, Blank, & Weltz, 2017; Elseroad & Rudd, 2011; Sebastian, Nissen, Sebastian, Meiman, & Beck, 2017b), but few have examined potential ways to control invasive annual grasses while simultaneously allowing seeding of native species that are also susceptible to herbicide (Clark, Sebastian, Nissen, & Sebastian, 2020; Eckert et al., 1974). Here we study two herbicides that differ in mode of action, soil persistence, and soil mobility to identify potential strategies that control invasive grasses without harming native species seeded for restoration.…”
Section: Introductionmentioning
confidence: 99%